2021
DOI: 10.1136/bmjgh-2020-004010
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use for acute respiratory infections among under-5 children in Bangladesh: a population-based survey

Abstract: IntroductionDespite acute respiratory infections (ARIs) being the single largest reason for antibiotic use in under-5 children in Bangladesh, the prevalence of antibiotic use in the community for an ARI episode and factors associated with antibiotic use in this age group are unknown.MethodsWe analysed nationally representative, population-based, household survey data from the Bangladesh Demographic and Health Survey 2014 to determine the prevalence of antibiotic use in the community for ARI in under-5 children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…Also supporting the concept that antibiotic use did not drive the disappearance of B. longum subsp. infantis , antibiotic use is prevalent in Bangladesh, where approximately 40% of children under the age of 5 with acute respiratory infection receive antibiotics [ 64 ]. Despite the high rate of antibiotic use, our work shows that colonization with B. longum subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Also supporting the concept that antibiotic use did not drive the disappearance of B. longum subsp. infantis , antibiotic use is prevalent in Bangladesh, where approximately 40% of children under the age of 5 with acute respiratory infection receive antibiotics [ 64 ]. Despite the high rate of antibiotic use, our work shows that colonization with B. longum subsp.…”
Section: Discussionmentioning
confidence: 99%
“…We reported output as the unadjusted odds ratio (OR) with 95% CI and p -value. We utilized the conceptual framework technique, which displayed the potential causal pathway and link between antibiotic use after admission and explanatory variables, including patient age, sex, comorbid conditions, smoking status, disease severity, and antibiotic use before hospital admission to delineate the causal relationship ( Figure 2 ) [ 46 ]. Technical details of the conceptual framework technique have been explained in Jewell et al [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is alarming since most pharmacies in Bangladesh are run by unqualified practitioners who provide antibiotics without a prescription [27]. Several studies have reported the overuse of antibiotics obtained from unqualified providers and drug shops in Bangladesh, and 80-90% of drug shops and medicine vendors operate without a license [8,13,19,28]. Additionally, the adequate supervision and inspection of drug outlets are complicated by the limited availability of drug inspectors (i.e., one drug inspector supervises 2236 pharmacy shops) [6].…”
Section: Discussionmentioning
confidence: 99%
“…We investigated seven associated factors with antibiotic usage in children with febrile illnesses based on existing literature [13,26,31,32,[36][37][38][39][40][41][42][43][44]. Explanatory variables utilised in this study are defined in Table 3.…”
Section: Explanatory Variablesmentioning
confidence: 99%
See 1 more Smart Citation